Contextual Based Learning Strategy Outing Class in Increasing Student Motivation to Realize Freedom of Learning - Handayani, Kustini; Bahri, Saiful (Universitas Tanjungpura, 2024)
The concept of independent learning is interpreted as independent learning which provides students with the opportunity to learn as comfortably as possible in a conducive and enjoyable but meaningful environment. Increasing learning motivation is one of the efforts that teachers can make to support independent learning. Outing class-based contextual learning strategies were chosen because when learning is always carried out in the classroom there is a tendency for students to feel bored, resulting in decreased motivation to learn. Outing classes provide children with the opportunity to learn directly and realistically, provide children with new learning experiences that are not available when studying in class, and are able to increase children's learning motivation. The aim of this outing class learning is basically to introduce children to nature and the environment around them. This research uses a descriptive qualitative research method, the data collection process is carried out using observation, documentation and interview techniques. The results of the analysis of increasing motivation show that basically motivation needs to be developed to help students analyze the relationship between the material being studied and their situation as individuals. The average response rate of respondents in this study was 88%. Outing class-based contextual learning strategies in increasing students' learning motivation need to be appreciated.